In Vivo Hypoglycemic Effect of Kigelia africana (Lam): Studies With Alloxan-Induced Diabetic Mice - Njogu, Stephen M. (J Evid Based Integr Med, 2018)
The claims by the traditional herbal medicine practitioners that Kigelia africana has bioactivity against several diseases, including diabetes mellitus, were investigated in this study. Type I diabetes mellitus was induced in mice by intraperitoneal administration of alloxan monohydrate followed by treatment with the therapeutic doses of the aqueous and ethyl acetate leaf extract of K africana to the experimentally diabetic mice. The treatment effects were compared with the normal control, diabetic control, and diabetic control rats treated with a standard antidiabetic drugs (insulin administered intraperitoneally at 1 IU/kg body weight in 0.1 mL physiological saline or glibenclamide administered orally at 3 mg/kg body weight in 0.1 mL physiological saline). Phytochemical composition of the leaf extract was assessed using standard procedures and mineral elements assessed using atomic absorption spectrophotometry and total reflection X-ray fluorescence system. Oral and intraperitoneal administration of the aqueous and ethyl acetate leaf extract caused a statistically significant dose-independent reduction in plasma glucose level in alloxan-induced diabetic mice. The observed hypoglycemic activity of this plant extract could be attributed to the observed phytochemicals and trace elements, which have been associated with exhibiting antidiabetic properties. Therefore, the data appear to support the hypoglycemic effects of K africana validating its folkloric usage.